Book Review. Issue 2 (1st November 2017) - Crawford, Amy
Time's Witnesses: Women's Voices from the Holocaust, Jakob Lothe (ed.) and Anne Marie Hagen (trans.) (2017) Edinburgh: Fledgling Press, 214 pp., ISBN: 9781905916900, p/bk, $11.99